A Comparative Study of Nutritional Health Mapping of Private and Government School Going Children Under 6-12 year - Singh, Pawani; Dwivedi, A.K.; Chakravorty, Sukanya (Journal of Neonatal Surgery, 2025)
Purpose: School is an important period for growth and development. Children's activities, diet, and nutrition all have an influence on their physical and cognitive development throughout this period. The present study will examine the nutritional condition of government and private school students aged 6 to 12 based on their eating patterns. Methods: A comparative cross-sectional study was done in both government and private school children, 100 students between the ages of 6 and 12 were interviewed about their eating habits, and they were asked to fill out a proforma as well as anthropometric measurement were taken. The data was analysed using appropriate statistical method. Result: Result of the study found that the prevalence of underweight is higher in government school pupils i.e. 40%, however in private school there is a 4% incidence of overweight is found and no incidence of overweight is detected in government school. Intake of more calories, salt, saturated fats, and sugar on a daily basis than students in public schools, raising their risk of sickness. Conclusion: Students attending government schools are more likely to suffer from undernutrition, while those attending private schools tend to be overweight and consume more unhealthy foods. In order to encourage healthy growth and avoid future health hazards, this emphasizes the necessity of customized dietary interventions in both school contexts